2009
DOI: 10.1155/2009/397910
|View full text |Cite
|
Sign up to set email alerts
|

Proteomic Analysis of Serum in Lung Cancer Induced by 3‐Methylcholanthrene

Abstract: Lung cancer remains the leading cause of cancer-related mortality worldwide. Early detection of lung cancer is problematic due to the lack of a marker with high diagnosis sensitivity and specificity. To determine the differently expressed proteins in the serum of lung cancer and figure out the function of the proteins, two-dimensional electrophoresis (2DE) and matrix-assisted laser desorption/ionization time-of-flight mass spectrometry (MALDI-TOF-MS) were used to screen the serum proteins of lung cancer model … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 54 publications
1
4
0
Order By: Relevance
“…Several lines of evidence suggested that increased blood Hp concentration reflects the disease stage of lung cancer []. Recent proteomic studies also reported an increased protein abundance of Hp in lung cancer []. In the current study, we found that HFD‐induced obesity greatly increased the protein levels of Hp in tumor‐bearing mice, which implies that impaired oxidative metabolism may occur in the lung of HFD‐fed mice.…”
Section: Discussionsupporting
confidence: 64%
“…Several lines of evidence suggested that increased blood Hp concentration reflects the disease stage of lung cancer []. Recent proteomic studies also reported an increased protein abundance of Hp in lung cancer []. In the current study, we found that HFD‐induced obesity greatly increased the protein levels of Hp in tumor‐bearing mice, which implies that impaired oxidative metabolism may occur in the lung of HFD‐fed mice.…”
Section: Discussionsupporting
confidence: 64%
“…This comparative approach is carried out to identify any proteins that may be upregulated or downregulated in a diseasespecific manner for eventual use as biomarkers of the abnormal state. Various cancer biomarkers are being tentatively identified using the proteome profiling approach, including lung, 6,7 ovarian, 8 prostate, 9 colorectal, 10 and liver cancers. 11 It is evident that proteomics is becoming an increasingly important tool for the identification of biomarkers and therapeutic targets for cancer and other diseases.…”
Section: Why Is the Study Of Proteomics Importantmentioning
confidence: 99%
“…Proteomics have been used widely for the identification of serum biomarkers for different types of cancers, such as prostate cancer 19–21, colorectal cancer 22–24, brain tumor 25, 26, breast cancer 27–30, liver cancer 31–33, pancreatic cancer 34, 35, ovarian cancer 36, 37, lung cancer etc. 38 (Table 1).…”
Section: Serum Proteomics For Biomarker Discoverymentioning
confidence: 99%